Cariotipo de células fetales en el diagnóstico prenatal en Costa Rica - Castro Volio, Isabel (1995)
The results of 182 genetic amniocenteses between 14 and 37 weeks gestation, frorn 1986 to 1992,.and of two cordocenteses in 1992, are reported. There were two main reasons for referral: maternal age 3S years and older and abnormal ultrasound assessment. Fetal cells were closed cultured and mass harvested. In 3.7% of cases fetal chrornosornes were defective. Tum around time was about three weeks up to and including 1991 arid two weeks in 1992, culture failure rate was 7% that year. No cytogenetic rnisdiagnosis and no cornplicatiOri or sequelae related to the amniocenteses were detected. We conclude this is a safe and reliable procedure to obtain fetal karyotypes and to irnprove obstetric managernent of high-risk pregnancies.